From STEM to Society: Lessons Learned from ARIS Broader Impact Project - Maleeha Shahid (The University of Alabama, 2024)
I participated in the "baseline study," examining 32 faculty research grant proposals from a variety of STEM (science, technology, engineering, mathematics) fields submitted by faculty across multiple departments on a single university's campus. We analyzed the broader impact statement in each of the 32 proposals using the Center for Advancing Research Impacts in Society (ARIS) broader impact (BI) Toolkit. This essay is a comprehensive review I attempted of BI strategies recommended by NSF and the ARIS Toolkit. My voice in this essay carries forward some of the impressions I perceived from interacting with NSF applicants' proposals submitted by the faculty at the study site. Moreover, the essay is set in the backdrop of my academic and professional background in medicine, public health, human resource administration, and heath communication and social influence. Views on cross-cultural comparisons are included with reference to broader impacts between United States and Pakistan as a developing nation.